2020
DOI: 10.1016/j.bja.2019.10.026
|View full text |Cite
|
Sign up to set email alerts
|

The posterior femoral cutaneous nerve contributes significantly to sensory innervation of the lower leg: an anatomical investigation

Abstract: Background: Incomplete peripheral nerve blocks distal to the popliteal region are commonly considered a sciatic and femoral/saphenous nerve block failure. The existence of a much more distal innervation area of the posterior femoral cutaneous nerve (PFCN) as described has not been assumed yet. We therefore investigated the distal termination of the PFCN in the lower leg. Methods: In 83 human lower extremities embalmed with Theil's method, the course of the PFCN was investigated from the sub-gluteal fold to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 11 publications
0
26
0
Order By: Relevance
“…These results might be owing to the rapid absorption rate of anesthetics by the epidural space during epidural anesthesia, which easily leads to an excessive anesthesia plane and subsequent fluctuations in the circulatory and respiratory functions during the perioperative period, manifesting as abnormal changes in hemodynamic indicators. The posterior lumbar plexus block can avoid the above shortcomings [ 17 ]. Meanwhile, the lumbar plexus involves the obturator, femoral, and lateral femoral cutaneous nerves.…”
Section: Discussionmentioning
confidence: 99%
“…These results might be owing to the rapid absorption rate of anesthetics by the epidural space during epidural anesthesia, which easily leads to an excessive anesthesia plane and subsequent fluctuations in the circulatory and respiratory functions during the perioperative period, manifesting as abnormal changes in hemodynamic indicators. The posterior lumbar plexus block can avoid the above shortcomings [ 17 ]. Meanwhile, the lumbar plexus involves the obturator, femoral, and lateral femoral cutaneous nerves.…”
Section: Discussionmentioning
confidence: 99%
“…In their studies of 83 human cadavers, popliteal ending of the PFCN was found in only 9.7% of the cases, whereas in 44.6% of the cases it was found to end within 10 cm of the most distal point of medial malleolus. In 13.2% of the cases, PFCN showed a close connection to the Achilles tendon [5]. The results of these cadaveric anatomical studies cannot be directly translated into clinical significance, given the fact that the vast majority of the patients tolerate BKA surgeries very well after receiving just saphenous and sciatic nerve blocks [6].…”
Section: Discussionmentioning
confidence: 99%
“…It is not commonly considered as a block target for surgical procedures below the knee. However, there is emerging anatomical evidence suggesting that PFCN may contribute to the sensory innervation of the posterior lower leg [5]. In this report, we present a case in which a combination of femoral and sciatic nerve blocks failed to provide adequate surgical analgesia in the posterior lower leg region for a patient who underwent below-the-knee amputation (BKA) and subsequent formalization surgery.…”
Section: Introductionmentioning
confidence: 99%
“…This nerve is the pure sensory nerve and has no motor innervations. The PFCN innervates the skin of the perineum, the posterior surface of the thigh, and various areas of the back of the leg (28,29).…”
Section: Functionmentioning
confidence: 99%